THE EFFECT OF BRAND IMAGE AND PRICE DECISION ON TOYOTA KIJANG INNOVA CAR CONSUMER PURCHASE DECISION PT. AGUNG AUTO MALL SUTOMO PEKANBARU - Kelvin Rizaldy; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT. Agung Auto Mall Sutomo Pekanbaru. The purpose of this study was to determine the effect of Brand Image and Pricing on Consumer Purchase Decisions of Toyota Kijang Innova Cars At. PT. Agung Auto Mall Sutomo Pekanbaru). Brand Image and Pricing as independent variables (X1,X2) while Consumer Purchasing Decisions as the dependent variable (Y). The problem in this research is that the sharp decline in sales be seen every year. It can be seen from the target and realization data of the company. The research sample was taken as many as 109 respondents from the population who were calculated using the Slovin formula. Data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS program. From the results of the tests conducted, it shows that Brand Image and Pricing have a positive and significant effect on Consumer Purchase Decisions for Toyota Kijang Innova Cars at PT. Agung Auto Mall Sutomo Pekanbaru Keywords: Brand Image, Pricing, Consumer Purchase Decisions